UMPSA researcher Dr. Noridayu helps evacuate flood victims - Nur Hartini, Mohd Hatta (UMPSA, 2023)
PEKAN, 4 December 2023 – Looking at the various problems that arise every time floods hit, a researcher and lecturer of the Faculty of Industrial Management (FPI), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), Dr. Noridayu Mah Hashim, 37, assisted and improved the process of evacuating flood victims through the evacuee model.